Respons Kultural Masyarakat Sasak Terhadap Islam - Asnawi Asnawi (Ulumuna, 2005)
Islam reached Lombok island at sixteenth century, approximately at 1545. Its well-known spreader was an expedition from Java led by Sunan Prapen son of Sunan Giri, one of the famous wali songo (nine religious leaders, the Islam spreader in Java). Before Islam reached this island, according to some historian, the indigenous Sasak—appellation to indigenous of Lombok people—had had their own traditional religion, Boda. Sometimes Boda was also called Majapahit Religion. Method of spreading Islam at early time of Islam in this island was called three-linked system. A religious leader coming from Java had to teach three indigenous people and then made them be religious leaders. After mastering what was taught they were considered religious leaders and, in turn, respectively have to teach another three candidates. This method of spreading gained effective outputs on one hand, but on other hand it also shaped a kind of viewpoint among indigenous people that the religious obligatories such as daily praying and fasting are only the duty of religious leaders not of common people. Such unexpected point of view in turn has polarized the people into two groups, religious leaders and their common disciples. The later have point of view that they only do what their religious leader and king ask them to do, and this was the embryo of a local Islamic syncretism known as Wetu Telu. After time of Sunan Prapen, the Tuan Guru—a special call to Lombokness religious leaders—take responsiblity on islamization in this island, especially to the Wetu Telu disciples.